SHORT- VS LONG-READ SEQUENCING OF SOIL ARTHROPODS - Sten Anslan (8288664) (2025)
This conference contribution was presented by Sten Anslan, Sirle Varusk, Kaarel Sammet, Manikandan Ariyan, Khairiah Mubarak Alwutayd. College of Science, Princess Nourah bint Abdulrahman University, Riyadh, Saudi Arabia, (18th Edition of the Qatar University Life Sciences Symposium Bio-Environment: Advances and Innovations. 2025). The characterization of soil arthropods traditionally follows morphological identifications of specimens extracted from soil, which is a highly laborious and time-consuming process. Metabarcoding has become an increasingly utilized approach for species identification from environmental DNA (eDNA) samples, and here, we examine the congruence of soil mite communities between morphological and two metabarcoding datasets. The morphological dataset was generated by extracting mite specimens from the soil samples, whereas molecular datasets represent two types of cytochrome c oxidase subunit I (COI) amplicons produced directly from soil eDNA and sequenced with Illumina (313 bp amplicons) and PacBio (658 bp amplicons) platforms. We found that specimen extraction from soil samples, followed by morphological identification, yielded the highest number of mite species. Despite significantly lower mite richness in the metabarcoding datasets, PacBio datasets (658 bp amplicons) provided more reliable community profiles that aligned strongly with the morphological data. This indicates that soil sample quantities generally used for microbial analyses are also informative in studying soil faunal communities. Other Information Conference information: 18th Edition of the Qatar University Life Sciences Symposium Bio-Environment: Advances and Innovations. (26 - 27 Nov 2025, Qatar University, Doha - Qatar) License: https://creativecommons.org/licenses/by/4.0/ See the conference information on the organizer's website: https://www.qu.edu.qa/en-us/conference/QULSS2025/Pages/default.aspx